Pengaruh Perubahan Set Point pada Pengendali Fuzzy Logic untuk Pengendalian Versi online (e-ISSN. 2252-620x) Suhu Mini Boiler - Bhakti Yudho Suprapto; Wahidin Wahab; Mgs. Abdus Salam (Jurnal Rekayasa Elektrika, 2013)
In this research, a mini boiler temperature control system is designed by using fuzzy logic controller (FLC). The FLC controls the valve of the incoming fuel. The mini boiler is fueled by gas, has length of 80 cm and diameter of 40 cm. FLC is designed in four different models based on the number of membership function of the temperature variable, i.e., three, five, seven and nine membership functions. The input variables are “temperature” and “error”, and the output variable is “valve”. There are two types of disturbance given to the control system, the disturbance of the system working at set point 125 °C, and disturbance by changing the set point values. In the first type, the FLC is able to reach 125 °C for all models. In the second type, the set points are varied to 100 °C, and 150 °C. At set point 125 °C and 150 °C, the FLC is able to achieve the pre-determined set points for all models. Mean while at set point 100 °C, the FLC can stabilized the system at point of 97.92 °C for the first model, and at the point of 100 °C for other models.